Biocrust Research in China: Recent Progress and Application in Land Degradation Control - Li, Xinrong; Hui, Rong; Tan, Huijuan; Zhao, Yang; Liu, Rentao; Song, Naiping (Frontiers in Plant Science, 2021)
Desert ecosystems are generally considered lifeless habitats characterised by extreme environmental conditions, yet they are successfully colonised by various biocrust no-vascular communities. A biocrust is not only an important ecosystem engineer and a bioindicator of desert ecological restoration but also plays a vital role in linking surficial abiotic and biotic factors. Thus, extensive research has been conducted on biocrusts in critical dryland zones. However, few studies have been conducted in the vast temperate deserts of China prior to the beginning of this century. We reviewed the research on biocrusts conducted in China since 2000, which firstly focussed on the eco-physiological responses of biocrusts to species composition, abiotic stresses, and anthropological disturbances. Further, research on the spatial distributions of biocrusts as well as their succession at different spatial scales, and relationships with vascular plants and soil biomes (especially underlying mechanisms of seed retention, germination, establishment and survival of vascular plants during biocrust succession, and creation of suitable niches and food webs for soil animals and microorganisms) was analysed. Additionally, studies emphasizing on the contribution of biocrusts to ecological and hydrological processes in deserts as well as their applications in the cultivation and inoculation of cyanobacteria for desertification control and ecological restoration were assessed. Finally, recent research on biocrusts was evaluated to propose future emerging research themes and new frontiers.